The potential of 1.5 T magnetic resonance imaging for the evaluation of fetal anomalies of the great vessels - Xie, Linjun; Xu, Hong; He, Xuelian; Fu, Hang; Zhang, Lu; Bai, Wei; Li, Xuesheng; Bao, Li; Xu, Huayan; Li, Xiaohong; Guo, Yingkun (Frontiers in Pediatrics, 2023)
Purpose: To determine the efficacy of 1.5T magnetic resonance imaging (MRI) for the diagnosis of anomalies of the fetal great arteries with comparison to fetal ultrasound, and to compare image quality between 1.5T and 3.0T MRI in fetal imaging of the great arteries. Methods: We compared the results of postnatal exam, or surgery and evaluated the application value of prenatal 1.5T MRI in the assessment of fetal great-vessel anomalies. To further determine the diagnostic potential of 1.5T MRI, 23 pregnant women with suspected fetal cardiovascular abnormalities who had undergone ultrasound and 3.0T MRI were enrolled and compared, respectively. Results: Prenatal MRI was superior to ultrasound in demonstrating aortic arch and branch abnormalities (sensitivity, 92.86% vs. 83.33%; specificity, 66.67% vs. 20%). The mean quality ratings for fetal MRI at 1.5T was higher than 3.0T (P < 0.001). Other than the fast scan speed afforded by 3.0T MRI, the signal noise ratio (SNR) of 1.5T MRI were higher than those of 3.0T MRI; however, the difference in contrast to noise ratio (CNR) between the two imaging modalities was not statistically significant. Conclusions: 1.5T MRI can achieve an overall assessment of fetal great-vessel anomalies, especially aortic arch and branch abnormalities. Therefore, 1.5T MRI can be considered a supplementary imaging modality for the prenatal assessment of extracardiac macrovascular malformations.